PENERAPAN FUZZY TIME SERIES DALAM MERAMALKAN JUMLAH WISATAWAN DI MASA PANDEMI COVID19 - MUSTAWINAR, BESSE HELMI; ADHALIA H, NURUL FUADY; SAM, MARWAN (E-Jurnal Matematika; Vol 11 No 3 (2022), 2022)
Tourism is one of Indonesia’s assets to promote economic growth. This sector became one of the largest contributors to national foreign exchange. The number of foreign tourist visits is an indicator of the contribution of tourism which has experiencing the upward trend in annually until the Covid19 happened. In this study, forecasting the number of foreign tourists is needed as a plan to improve the quality of tourism during the pandemic. We used Fuzzy Time Series (FTS) Cheng method. The actual data processed comes from the Central Statistics Agency from April 2020 through December 2021. Based on forecasting results, the performance of the forecasting model is in the very good category with Mean Absolute Percentage Error (MAPE) value is 5.06%. It means that our predictions are on average 5.06% away from the actual values they were aiming for. In other side, we have forecasting accuracy value is 94.94% which means that the forecast values were close to the actual. Keywords :  Tourist, FTS, Cheng Methods